Delivery at Catholic hospitals and postpartum contraception use, five US states, 2015–2018. Issue 1 (13th February 2022) - Menegay, Michelle C.; Andridge, Rebecca; Rivlin, Katherine; Gallo, Maria F.
Abstract: Objectives: To evaluate whether the prevalence of postpartum contraceptive use was lower among people who delivered at a Catholic hospital compared to a non‐Catholic hospital. Methods: We linked 2015–2018 Pregnancy Risk Assessment Monitoring System (PRAMS) survey data from five states to hospital information from the corresponding birth certificate file. People with a live birth self‐reported their use of contraception methods on the PRAMS survey at 2–6 months postpartum, which we coded into two dichotomous (yes vs. no) outcomes for use of female sterilization and highly‐effective contraception (female/male sterilization, intrauterine device, implant, injectable, oral contraception, patch, or ring). We conducted multilevel log‐binomial regression to examine the relationship between birth hospital type and postpartum contraception use adjusting for confounders. Results: Prevalence of female sterilization for people who delivered at a Catholic hospital was 51% lower than that of their counterparts delivering at a non‐Catholic hospital (adjusted prevalence ratio: 0.49; 95% confidence interval: 0.37–0.65). Conclusion: We found lower use of postpartum female sterilization, but no difference in highly effective contraception overall, for people who delivered at a Catholic hospital compared to a non‐Catholic hospital.